Permanências e rupturas nas práticas de professoras alfabetizadoras em formação: reflexões a partir do PNAIC (2013) - León, Silvana Corrêa Vieira De (Universidade do Vale do Rio dos Sinos, 2015)
The object of interest in this investigation is the formation program known as PNAIC – Pacto da Alfabetização na Idade Certa – from the year 2013, when language was the focus of the activities (alphabetization and literacy), from the perspective of literacy teachers in formation, from a municipal school in the Vale do Rio dos Sinos´ region. The analysis was guided by the following question: is it possible to perceive the impacts on the process of teaching a mother tongue, when it comes to their practices, and considering that they have been under continued formation, specifically by the PNAIC program, in a municipal school in the Vale do Rio dos Sinos´ region? In order to do it, the main objective is to verify to what extent the continued formation emerges from the speeches of the teachers, considering their own practices, from the second and third grades in the Elementary School. The methodology adopted was the qualitative research. The instruments used to gather the data were: i) an analysis of the formation material from PNAIC, unities 1 and 3 from each manual that integrate the alphabetization cycle, observing the concepts of alphabetization, literacy and the alphabetical writing system; (ii) semi-structured and audio-recorded interviews with 4 teachers coursing the PNAIC. The theoretical basis that support the investigation are Bakhtin (2003, 2006), Kleiman (2004, 2005, 2007), Mortatti (2000, 2006), Soares (2005, 2010, 2013), Vygotsky (1996, 1998). Amongst the findings in this study is the importance evidenced by programs of continued formation, like the PNAIC, when it comes to conceive the activity of the teacher of alphabetization from the perspective of a reflexive action in order to obtain positive results in pedagogical practices. When it comes to the manuals, as well as the dynamics of the formation process, some proposals devoted to the teaching of writing and reading were noticed through the usage of diversified didactical material provided by MEC. The observation of the speeches provides by the teachers evidenced the significant construction of concepts debated in the formation course that signalled to changes in their pedagogical practices.
Keywords: Alfabetização; Letramento; Formação continuada; PNAIC; Alphabetization; Literacy; Continued formation; ACCNPQ::Lingüística, Letras e Artes::Lingüística